Accounting in Macau: A Historical Perspective from 1970s until 2008 - Lam, Ching Chi (University of Saint Joseph, 2011)
The current research study embraced the objectives to investigate the transformation of accounting in Macau from the first set of accounting legislations in 1970s, through the first set of accounting standards in 1983, until a year after the first application of international accounting standards, by 2008. From the transformation, the role taken by accounting in the economy and the factors that have influenced the transformation were intended to identify. Through the historical picture, findings have supported and expanded the theoretical concepts that accounting was taking both active and passive roles in the economy. Furthermore, they also supported the theoretical concepts that culture, economic environment, political environment and education influenced the transformation of accounting. The objectives have been structured through three research issues identified from the analysis of past literatures. Five qualitative and quantitative research studies have been carried out, using primary and secondary data from both primary and secondary sources. In-depth interviews on 13 representative respondents of the government, the profession, the industry and the academia, directly or in-directly related with accounting have been done. A case study on a company doing business in Macau since 1970s was included to enrich, supplement and evaluate the findings on the accounting practice of Macau. Based on the findings, a model has been constructed that represented the interaction between accounting and the different factors of the economy. Contributions from the research findings have enriched the research literatures on the area of accounting history. Implications from the findings have generated better insights for the business and economic histories of Macau
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

Aid and poverty reduction: comparing China and France's aid policies and projects in Guinea - Diakité, Ansoumane Douty (University of Saint Joseph, 2016)
The purpose of this research is to analyse the nexus between foreign aid and poverty reduction. In this research, aid provided by traditional and (re)emerging donors, China and France, was compared to understand their strategies toward poverty reduction and the impact of their aid in improving the conditions of their beneficiaries. Guinea, a Least Developed Country, was used as unit of comparison and assessment. Qualitative research methodology was used to collect data about the two aid donors, China and France. Among other research tools used, there are documents’ analysis (official documents from donors and recipients, declarations, scholarly works, media articles, etc.), interviews with various stakeholders, site visits and observation. As for main findings, this research found similarities and differences between China and France’s aid strategies in general and in Guinea in particular. There are similarities in the ways they integrate poverty reduction into their aid policies, motives and partly in their geographical and sectoral allocation systems. In terms of differences, they use different instruments and conditions to deliver their aid for poverty reduction. Regarding the impact of their aid, both donors have to some extent contributed to improving the access of the poor population in Guinea to basic services such as education, health, water and sanitation, etc. Finally, contrary to those who have denied the importance of foreign aid as a financial tool to reduce poverty, this research posits that aid is still a relevant tool to address poverty. However, more work needs to be done at donor, recipient and direct beneficiaries’ levels to ensure its effectiveness. On the other hand, it posits that the divide between traditional and (re)-emerging donors is becoming blurred as their strategies to address poverty are becoming increasingly alike
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

Banking efficiency and competition: an empirical research on Macau's banking industry - Lei, Hoi Kin (University of Saint Joseph, 2019)
This research examines the relationship between banking competition and efficiency using relevant data of Macau banking industry from 1999 to 2016. The key finding of this research is to demonstrate a clear causality between competition and efficiency in Macau’s banking industry throughout the study period. The interaction between two vital factors of the banking industry provides a solid empirical evidence for the practitioners and policymakers to make sound decisions accordingly. The most recent data show that there is a wide variation of key operational indicators of different banks in 2016. However, this study finds no evidence that the size of operations in terms of total bank loans would impact banks’ efficiency. Economies of scale or market share doesn’t necessarily bring cost efficiency in Macau’s banking industry
Keywords: Doctorate of Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Dutch Disease In Macau: Theoretical Modeling, Empirical Diagnosis And Treatments - Mieiro, Susana Margarida Baptista (University of Saint Joseph, 2013)
Keywords: Dutch Disease; Macau

Lusophone-African multinational enterprises internationalization mode: a case analysis of Angolan and Mozambican enterprises - Gonçalves, Marcus Vinicius Amaral (University of Saint Joseph, 2017)
Several internationalization theories have been developed over the past few decades that have made great contributions in explaining enterprise internationalization and their mode of entry strategy. It has been suggested that the determinants of entry mode choice of enterprises from emerging and frontier markets differ from those of comparable enterprises from advanced economies. Literature review appears to indicate that there is a need to expand the framework for entry mode strategies to accommodate the expansion issues enterprises from emerging and frontier countries face in the global marketplace. Nevertheless, not much information and acceptable conclusion has been made on how MNEs from frontier markets internationalize and what factors influence their choice of entry into those markets. This study investigated the internationalization strategies of Lusophone Africa MNEs from Angola and Mozambique, more specifically their entry mode. Information was gathered through a survey of 29 MNE’s upper management respondents and subsequent face-to-face semi-structured interviews with 24 of them in their countries. The results of this study suggest that most MNEs opted for equity-based investment strategies, mainly joint venture and M&E as their preferred mode of entry when internationalizing. A significant group of them opted for e- commerce/e-business strategies, and direct and indirect exports. A smaller portion of the interviewees chose Greenfield investment as a mode of entry. Many of these MNEs could be classified as born global/INV. Finally, this study presents a conceptual framework for use in studying the entry mode choice of enterprises from Lusophone Africa frontier markets and presents research propositions for better understanding the determinants of entry mode strategies of enterprise from Angola and Mozambique. Keywords: Internationalization, Entry Mode, Emerging Markets, Frontier Markets, Lusophone African MNEs, Angola, Mozambique
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Subjective Wellbeing And Quality of Work Life in Macau - Rato, Ricardo Jorge Parreira (University of Saint Joseph, 2013)
Keywords: China; Macau (Special Administrative Region); Quality of life; Research

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny Oliveros Lao (University of Saint Joseph, 2018)
This dissertation reports on a study which aims to add to the theoretical understanding of how social capital is transferred from one generation to the next in business families. Studies in the field of family business have emphasized the importance of succession for the survival of family businesses, but while the succession process and planning have been widely studied, the examination of social capital succession is scarce. As for the studies in family business’s social capital, the importance of social capital as a source of competitive advantage which already exists in business families have often been expressed, but there is a lack of research in the means of transferring this form of capital from the family business leaders to their successors. The study presented here addresses this gap in family business succession literature and social capital literature, explaining the means of transgenerational succession of social capital in family businesses. This is a qualitative research using the multiple case study method which aims to investigate the means of social capital transmission by comparing the cases of five different Chinese family businesses in Macau, which are in the succession process, with the successor currently managing the firm while the former generation business leaders are in the process of handing over the business and preparing for retirement. In doing so, this research offers a theoretical framework of explaining how social capital is transmitted from the incumbents to the successors throughout a five-stage succession process developed for this research. The forms of social capital that exists in family businesses are identified from previous literature, in order to clearly explain how these different forms of social capital are passed on from generation to generation based on the review on succession process introduced in published literature. A theoretical iii framework is formed from the two parent theories on family business succession and social capital, and is then verified empirically from five Chinese family businesses in Macau. The cases are developed through in-depth interviews with the incumbents and successors of the family businesses, informal interviews with stakeholders (including family members, business associates, non-family employees and customers), direct observation on the premises of the Chinese family businesses and secondary data, in order to study the process of intergenerational transmission of social capital in these Chinese family businesses
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

The influence of bilateral trade agreements on mode of market entry choice of resources seeking Chinese firms operating in Nigeria - Olukayode, Iwaloye Ojo (University of Saint Joseph, 2014)
In the past three decades there have being an increase in the number of Bilateral Trade Agreements (BTAs) globally. These agreements involve huge human and financial movements and are essentially based on trade and investment. This phenomenon has brought new dimension to global business environment by changing the landscape in whichfirms from emerging markets operate in another emerging market. In the light of this, this dissertation is to examine how bilateral trade agreementsprovisions influence choice of foreign market entry mode of resource seeking Chinese Multinational Enterprises operating in Nigeria. This study adopts a qualitative design, collecting data using semi-structured interviews. The data are analyzed with content analysis and explanation building to identify themes through application of replication logic. The data obtained from the interviews regarding the research questions are presented and discussed as major findings and adoptedfor the creation of the new model for the study of resources seeking firm’s choice of market entry modes in emerging markets The model developed in this dissertation makes a contribution to theory for the study of market entry modes of MNEs from developing countries entering another developing country. In this case, Chinese resources seeking multinational firms entering Nigeria. Elements of Dunning’s OLI theory, Resources Dependency Theory, and Institution theory extended for the purpose for the theory development process. This investigation also provides important information to assist state policy actors in their development of bilateral trade agreements between China and Nigeria. Implications for firms and their involvement in developing countries and with framework where bilateral trade agreements exist are also provided
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Understanding Employee Turnover in Multi-Cultural High Demand Situations: The Hotel Service Industry in Macau (2008-2012) - Lo, Ka In (University of Saint Joseph, 2013)
Keywords: 2008-2012; Hotel Service Industry; Macau